2017
DOI: 10.1038/srep41401
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and autonomic function and structure in footpads of a diabetic mouse model

Abstract: Sensory and autonomic neuropathy affects the majority of type II diabetic patients. Clinically, autonomic evaluation often focuses on sudomotor function yet this is rarely assessed in animal models. We undertook morphological and functional studies to assess large myelinated and small unmyelinated axons in the db/db type II diabetes mouse model. We observed that autonomic innervation of sweat glands in the footpads was significantly reduced in db/db mice compared to control db/+ mice and this deficit was great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 64 publications
(79 reference statements)
2
36
0
Order By: Relevance
“…Many pivotal studies over the past 10 years have eloquently and thoroughly demonstrated the role of the PI3K/AKT/mTOR pathway on SC myelination in vivo (Beirowski et al, 2017;Cotter et al, 2010;Figlia et al, 2017;Goebbels et al, 2012;Norrmén et al, 2014Norrmén et al, , 2018Sherman et al, 2012 Gregorio et al, 2018;Liu et al, 2017;O'Brien et al, 2014;Sullivan et al, 2007). Consistent with diabetic models, we did not observe reduced CMAP amplitude or motor strength/coordination in INSR/IGF1R SCKO mice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Many pivotal studies over the past 10 years have eloquently and thoroughly demonstrated the role of the PI3K/AKT/mTOR pathway on SC myelination in vivo (Beirowski et al, 2017;Cotter et al, 2010;Figlia et al, 2017;Goebbels et al, 2012;Norrmén et al, 2014Norrmén et al, , 2018Sherman et al, 2012 Gregorio et al, 2018;Liu et al, 2017;O'Brien et al, 2014;Sullivan et al, 2007). Consistent with diabetic models, we did not observe reduced CMAP amplitude or motor strength/coordination in INSR/IGF1R SCKO mice.…”
Section: Discussionsupporting
confidence: 82%
“…With time, the mice develop severe hyperglycemia and insulin resistance. BKS db/db mice have reduced NCV, reduced sensitivity to heat (tail flick test), reduced sensitivity to touch (Von Frey test), reduced SNAPs amplitude, and reduced SNAP conduction velocity (SNAP CV) (De Gregorio, Contador, Campero, Ezquer, & Ezquer, ; Liu et al, ; O'Brien et al, ; Sullivan et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, autonomic motor neuron damage occurs long patients report somatic sensory symptoms. This is supported by the finding that in diabetic mice, thin, non-myelinated post ganglionic autonomic motor neurons show deficits long before somatic sensory motorneurons do (Liu et al 2017). Neuropathic lesions can affect various autonomic pathways resulting in gastroparesis (Vinik et al 2003), cardiovascular dysregulation (Vinik et al 2003, 2011), sudomotor dysfunction (Liu et al 2017), diabetic cystopathy (Faerman et al 1971; Frimodt-Moller 1980; Kaplan et al 1995; Vinik et al 2003), and dysregulation of blood flow in the periphery (UKPDS 1998).…”
Section: Introductionmentioning
confidence: 74%
“…et al 2016). In addition, diabetic complications are age dependent (Gunnarsson 1975; DCCT Research Group 1996; Liu et al 2017). This age dependence combined with the 111.5% increase in persons age 65 and older from 1975-2015 (United States.…”
Section: Introductionmentioning
confidence: 99%